Bibliometric analysis of studies on threat assessment and prioritization of species for conservation - Wani, Zishan Ahmad; Pant, Shreekar; Bhat, Jahangeer A.; Tariq, Mohd; Siddiqui, Sazada; Alshaharni, Mohammed O. (Frontiers in Forests and Global Change, 2024)
The present study investigated the evolution and current situation of research on threat assessment and prioritization of species for conservation at a global level by analyzing bibliometrically the most relevant and productive authors, sources, and countries, most cited papers, country collaborations and most frequent keywords as reflected in the scientific literature using the Web of Science database. From 1989–2022, a total of 315 relevant documents were retrieved from 129 sources. Results revealed that since 1989, there has been an increase in the number of publications on threat assessment and prioritization of species for conservation. A total of 1,300 authors have contributed to the field through their research contributions. Among the 129 sources, the journals ‘Biodiversity and Conservation’ and ‘Biological Conservation’ are the most relevant and productive. Among countries, the USA has produced the highest number of publications, whereas Benin has the highest Multiple Country Production with a rate of 71.4%. Among the authors, ‘Keith DA’ has received the most citations, and among the sources, the journal ‘Biological Conservation’ received the highest number of citations. Conservation, biodiversity, conservation priorities, species richness, and threatened species are the most frequently used keywords and follow power-law distribution. The present study will be useful to the researchers in determining which journals to target and how to identify potential research partners in the concerned field. It is recommended that institutions in developed countries be encouraged to lead research programs in developing and underdeveloped countries so that such studies will be carried out at local, regional, and global scale, as biodiversity loss is a global issue.